Computational and experimental pharmacology to decode the efficacy of Theobroma cacao L. against doxorubicin-induced organ toxicity in EAC-mediated solid tumor-induced mice - Patil, Priyanka P.; Kumar, Pranjal; Khanal, Pukar; Patil, Vishal S.; Darasaguppe, Harish R.; Bhandare, Vishwambhar Vishnu; Bhatkande, Arati; Shukla, Sudhanshu; Joshi, Rajesh K.; Patil, Basanagouda M.; Roy, Subarna (Frontiers in Pharmacology, 2023)
Background and objective: Doxorubicin is an extensively utilized chemotherapeutic drug and it causes damage to the heart, liver, and kidneys by oxidative stress. Theobroma cacao L. (cocoa) is reported to possess protective efficacy against several chemical-induced organ damages and also acts as an anticancer agent. The study is aimed to determine whether the administration of cocoa bean extract reduces the doxorubicin-induced organ damage in mice with Ehrlich ascites carcinoma (EAC) without compromising doxorubicin efficacy. Methodology: Multiple in vitro methods such as cell proliferation, colony formation, chemosensitivity, and wound healing assays were carried out on cancer as well as normal cell lines to document the effect of cocoa extract (COE) on cellular physiology followed by in vivo mouse survival analysis and the organ-protective effect of COE on DOX-treated animals with EAC-induced solid tumor was then investigated. In silico studies were conducted on cocoa compounds with lipoxygenase and xanthine oxidase to provide possible molecular explanations for the experimental observations. Results: In vitro, studies revealed potent selective cytotoxicity of COE on cancer cells compared to normal. Interestingly, COE enhanced DOX potency when used in combination. The in vivo results revealed reductions in EAC and DOX-induced toxicities in mice treated with COE which also improved the mouse survival time, percentage of life span, antioxidant defence system, improved renal, hepatic, and cardiac function biomarkers, and also oxidative stress markers. COE reduced DOX-induced histopathological alterations. Through molecular docking and MD simulations, we observed chlorogenic acid and 8’8 Methylenebiscatechin, present in cocoa to have the highest binding affinity with lipoxygenase and xanthine oxidase which lends support to their potential in ameliorating oxidative stress. Conclusion: The COE reduced DOX-induced organ damage in EAC-induced tumor model and exhibited powerful anticancer and antioxidant effects. Therefore, COE might be useful as an adjuvant nutritional supplement in cancer therapy.